Unfolding Role of a Danger Molecule Adenosine Signaling in Modulation of Microbial Infection and Host Cell Response - Lee, Jaden S. (Int J Mol Sci, 2018)
Ectonucleotidases CD39 and CD73, specific nucleotide metabolizing enzymes located on the surface of the host, can convert a pro-inflammatory environment driven by a danger molecule extracellular-ATP to an adenosine-mediated anti-inflammatory milieu. Accordingly, CD39/CD73 signaling has been strongly implicated in modulating the intensity, duration, and composition of purinergic danger signals delivered to host. Recent studies have eluted potential roles for CD39 and CD73 in selective triggering of a variety of host immune cells and molecules in the presence of pathogenic microorganisms or microbial virulence molecules. Growing evidence also suggests that CD39 and CD73 present complimentary, but likely differential, actions against pathogens to shape the course and severity of microbial infection as well as the associated immune response. Similarly, adenosine receptors A(2A) and A(2B) have been proposed to be major immunomodulators of adenosine signaling during chronic inflammatory conditions induced by opportunistic pathogens, such as oral colonizer Porphyromonas gingivalis. Therefore, we here review the recent studies that demonstrate how complex network of molecules in the extracellular adenosine signaling machinery and their interactions can reshape immune responses and may also be targeted by opportunistic pathogens to establish successful colonization in human mucosal tissues and modulate the host immune response.